2014
DOI: 10.1158/1940-6207.capr-14-0097
|View full text |Cite
|
Sign up to set email alerts
|

Widefield Optical Imaging of Changes in Uptake of Glucose and Tissue Extracellular pH in Head and Neck Cancer

Abstract: The overall objective of this study is to develop an optical imaging approach to simultaneously measure altered cell metabolism and changes in tissue extracellular pH with the progression of cancer using clinically isolated biopsies. In this study, 19 pairs of clinically normal and abnormal biopsies were obtained from consenting head and neck cancer patients at UCDMC. Fluorescence intensity of tissue biopsies before and after topical delivery of 2-NBDG (2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Consequently, we used intravital MPM to monitor the cellular uptake of the fluorescent glucose analog 2-NBDG as a complement to PET for examining cellular glucose tracer uptake in the living animal. Similar to 18 F-FDG in PET, 2-NBDG in optical microscopy has experienced growing application for both preclinical and clinical studies of cancer (8,16,21). Our findings with 2-NBDG and intravital MPM in the proximal tubule of rodents were parallel to our findings with 18 F-FDG and PET in the cortex of the kidney.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consequently, we used intravital MPM to monitor the cellular uptake of the fluorescent glucose analog 2-NBDG as a complement to PET for examining cellular glucose tracer uptake in the living animal. Similar to 18 F-FDG in PET, 2-NBDG in optical microscopy has experienced growing application for both preclinical and clinical studies of cancer (8,16,21). Our findings with 2-NBDG and intravital MPM in the proximal tubule of rodents were parallel to our findings with 18 F-FDG and PET in the cortex of the kidney.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, we employed positron emission tomography (PET) and intravital multiphoton microscopy (MPM) to assess cortical and proximal tubule glucose tracer uptake, respectively, following experimental perturbations of kidney metabolism. Applying dynamic image acquisition PET with [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] fluoro-2-deoxyglucose ( 18 F-FDG) and tracer kinetic modeling, we found that an intracellular compartment in the cortex of the kidney could be distinguished from the blood and urine compartments in animals. Given emerging literature that the tumor suppressor protein p53 is an important regulator of cellular metabolism, we demonstrated that PET imaging was able to discern a threefold increase in cortical 18 F-FDG uptake following the pharmacological inhibition of p53 in animals.…”
mentioning
confidence: 99%
“…bladder cancer | fluorescence-guided surgery | NIR imaging | acidity | human tissue B ladder cancer is the fifth most common cancer, constituting 4.5% of all new cancer cases in the United States; 76,960 new cases were estimated in 2016, and the death rate currently expected from bladder cancer is 21% (16,390). Approximately 2.4% of men and women will be diagnosed with bladder cancer at some point during their lifetime.…”
mentioning
confidence: 99%
“…pH low insertion peptides (pHLIPs) are a class of membrane-binding peptides that specifically target acidic cells in vitro and in vivo (11) by inserting across cellular membranes when the extracellular pH is low (12). pHLIPs conjugated with fluorescent dyes have been used to differentiate normal from neoplastic tissue in various animal tumor models (12)(13)(14)(15) and in human biopsy head and neck samples (16,17). This report uses an indocyanine green (ICG) pHLIP conjugate for the diagnosis of urothelial carcinoma and precancerous lesions in fresh human radical cystectomy samples ex vivo and points the way toward a wide range of diagnostic and therapeutic alternatives.…”
mentioning
confidence: 99%
“…Clinical applications have focused on the topical application of pHLIP onto biopsies from human head and neck cancer patients, where pHLIP detected cancerous tissue within the samples (46,47).…”
mentioning
confidence: 99%